Comparison of physician- and self-assessed pubertal onset in Japanese children - Saito-Abe, Mayako; Nishizato, Minaho; Yamamoto-Hanada, Kiwako; Yang, Liming; Fukami, Maki; Ito, Yoshiya; Ihara, Kenji; Iwabuchi, Atsushi; Okamoto, Shingo; Naiki, Yasuhiro; Ohya, Yukihiro; Horikawa, Reiko (Frontiers in Pediatrics, 2023)
Physical examinations to assess pubertal development are challenging in large epidemiological surveys. This study aimed to assess the reliability of judgment of pubertal onset in Japanese children by the original pubertal self-assessment sheet. A total of 144 children aged 10 or 12 years were recruited between March 2019 and September 2020 from the pediatric endocrine outpatient clinics of participating institutions. Agreement between the physician- and participant-assessed pubertal onsets was determined using unweighted kappa (UK) and Gwet’s agreement coefficient (AC1). The physician’s assessment of pubertal onset was in slight agreement with that of the self-assessment sheet in 10-year-old boys (UK: 0.23 and AC1: 0.14), whereas the agreement between the physician’s assessment and self-assessment sheet results was good and the physician’s assessment was fair (UK: 0.64 and AC1: 0.94) in 12-year-old boys. The physician’s assessment of pubertal onset were in good and moderate agreement with the self-assessment sheet in 10-year-old girls (UK/AC1: 0.74/0.78, respectively). In 12-year-old girls, although it showed　poor agreement with UK (0.46), there was a very good agreement with AC1 (0.88). Although self-assessment of breast development was in good agreement with that of the physician’s assessment for determining pubertal onset in girls, large-scale epidemiological studies are difficult to conduct for adolescent boys, especially for those in the early pubertal stage.